Comparative Genome Analysis of Three Thiocyanate Oxidizing Thioalkalivibrio Species Isolated from Soda Lakes - Berben, Tom; Overmars, Lex; Sorokin, Dimitry Y.; Muyzer, Gerard (Frontiers in Microbiology, 2017)
Thiocyanate is a C1 compound containing carbon, nitrogen and sulfur. It is a (by)product in a number of natural and industrial processes. Because thiocyanate is toxic to many organisms, including humans, its removal from industrial waste streams is an important problem. Although a number of bacteria can use thiocyanate as a nitrogen source, only a few can use it as an electron donor. There are two distinct pathways to use thiocyanate: (i) the “carbonyl sulfide pathway”, which has been extensively studied, and (ii) the “cyanate pathway,” whose key enzyme, thiocyanate dehydrogenase, was recently purified and studied. Three species of Thioalkalivibrio, a group of haloalkaliphilic sulfur-oxidizing bacteria isolated from soda lakes, have been described as thiocyanate oxidizers: (i) Thioalkalivibrio paradoxus (“cyanate pathway”), (ii) Thioalkalivibrio thiocyanoxidans (“cyanate pathway”) and (iii) Thioalkalivibrio thiocyanodenitrificans (“carbonyl sulfide pathway”). In this study we provide a comparative genome analysis of these described thiocyanate oxidizers, with genomes ranging in size from 2.5 to 3.8 million base pairs. While focusing on thiocyanate degradation, we also analyzed the differences in sulfur, carbon and nitrogen metabolism. We found that the thiocyanate dehydrogenase gene is present in ten different Thioalkalivibrio strains, in two distinct genomic contexts/genotypes. The first genotype is defined by having genes for flavocytochrome c sulfide dehydrogenase upstream from the thiocyanate dehydrogenase operon (present in two strains including the type strain of Thioalkalivibrio paradoxus), whereas in the second genotype these genes are located downstream, together with two additional genes of unknown function (present in eight strains, including the type strains of Thioalkalivibrio thiocyanoxidans). Additionally, we found differences in the presence/absence of genes for various sulfur oxidation pathways, such as sulfide:quinone oxidoreductase, dissimilatory sulfite reductase, and sulfite dehydrogenase. One strain (Thioalkalivibrio thiocyanodenitrificans) lacks genes encoding a carbon concentrating mechanism and none of the investigated genomes were shown to contain known bicarbonate transporters. This study gives insight into the genomic variation of thiocyanate oxidizing bacteria and may lead to improvements in the application of these organisms in the bioremediation of industrial waste streams.